Determinants of Demand for Health Card in Thailand - Supakankunti, Siripen (World Bank, Washington, DC, 2013)
The health insurance card scheme was introduced as the Health Card Project (HCP) in 1983. This program was based on the risk sharing of health expenditures with no cost sharing in a voluntary health insurance prepayment scheme. Frequent adjustments in both the strategies and objectives of the program have included voluntary risk sharing with cost recovery in addition to service provision. The HCP needs a large enough number of enrollees to ensure a sufficient pool of risks. However, the newly elected government of Thailand has committed to rapidly extending health care coverage to all Thai citizens. Even though the HCP was suppressed and replaced by this program in October 2001, this study of the determinants of demand for the prepaid health card is still important. The HCP can be assessed as relatively progressive, serving rural areas, poor and near poor groups. This study has found that employment, education, and the presence of illness are significant factors influencing card purchase. The third factor is related to the problem of adverse selection of the program; families with symptoms of sickness are more likely to buy cards and increase their use of health services. The results also show an improvement in accessibility to health care and a high level of satisfaction among cardholders, both key objectives of the program. Problems of program performance include issues of program and financial management: marketing, quality control and cost recovery; ineffective referral systems, and lack of limits on episodes and ceilings for expenses. There is a need for an efficient and consistent health policy, which would involve revised criteria for card use, standard reimbursement agreements with hospitals, government subsidies, and an overall strengthening of the program.